3-2(x-1)+4x=5-(2-x)

Simple and best practice solution for 3-2(x-1)+4x=5-(2-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-2(x-1)+4x=5-(2-x) equation:


Simplifying
3 + -2(x + -1) + 4x = 5 + -1(2 + -1x)

Reorder the terms:
3 + -2(-1 + x) + 4x = 5 + -1(2 + -1x)
3 + (-1 * -2 + x * -2) + 4x = 5 + -1(2 + -1x)
3 + (2 + -2x) + 4x = 5 + -1(2 + -1x)

Combine like terms: 3 + 2 = 5
5 + -2x + 4x = 5 + -1(2 + -1x)

Combine like terms: -2x + 4x = 2x
5 + 2x = 5 + -1(2 + -1x)
5 + 2x = 5 + (2 * -1 + -1x * -1)
5 + 2x = 5 + (-2 + 1x)

Combine like terms: 5 + -2 = 3
5 + 2x = 3 + 1x

Solving
5 + 2x = 3 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + 2x + -1x = 3 + 1x + -1x

Combine like terms: 2x + -1x = 1x
5 + 1x = 3 + 1x + -1x

Combine like terms: 1x + -1x = 0
5 + 1x = 3 + 0
5 + 1x = 3

Add '-5' to each side of the equation.
5 + -5 + 1x = 3 + -5

Combine like terms: 5 + -5 = 0
0 + 1x = 3 + -5
1x = 3 + -5

Combine like terms: 3 + -5 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| -2/3(6x-12y) | | 9(t-9)-11=-6t+10 | | 5w+2=-1+3(w-10) | | X/3-21=14 | | 4-2(3x-5)+x=7-(1-3x) | | X/6-17=14 | | 3x-2(x+4)=2x-3 | | 5x+-5=20 | | 8W+2W-7=23 | | 7+4x-4t=-11 | | 19x-13=25 | | 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) | | 2x+3(1x-10)=45 | | (x^2+1)= | | 2x+3(x-10)=-45 | | y=-0.2*x+520.4 | | 1x-5(x+2)=26 | | 6*6+7= | | 2sen^2x-senx-1=0 | | 5/678 | | 5/6.35 | | 5/6•35 | | 2y-50+5y-17=180 | | 3=5-3/4 | | 5x-8(x+5)= | | 3x(x+0)=0 | | 1/3,4 | | 2x+3=-(x+1) | | 3(k-6)-(-3k-8)=5k |

Equations solver categories